O ar puro e a responsabilidade comum, mas diferenciada: elementos de um regime em construção - Mostaço, Gabriel Marques (2020)
Clean air is a common resource and should be treated through the legal status of common concern of humankind. As a natural element, the air is essential to the existence and maintenance of life with dignity, a concept that aggregates dimensions of economic, social, cultural, and environmental rights to the underlying right to life in the international regime. Air pollution, or polluted air, is the opposite to clean air, and compromises the quality of life at a local, regional, and global level, with adverse impacts for current and future generations. Therefore, the complexity of air pollution requires an identical formulation of the legal system, that should adapt its propositions through new interactions with legal and social values of solidarity and equity. In this research, we aim to analyze common but differentiated responsibilities of States, that emerge from the concept of the common heritage of mankind and the sustainable development principle. To do so, we intend to provide interactions between common obligations (based in solidarity) and differentiation (based in equity) of developed and developing States, within the clean air regime, especially to treat the effects of long-range transboundary air pollution. Further, it should analyze main forms of differentiation in international law, such as the substantive differentiation or the flexibility of obligations, the concession of favorable compliance, timetable, and financial or technological contributions. In terms of methodology, this research follows the dialogue of legal sources to provide a complex approach to clean air, within national and international law regimes. Lastly, it articulates theoretical references of clean air in international and domestic Brazilian law, aiming to retrace some relevant fragments of its regime to apply concepts such as the common but differentiated responsibilities for its effectiveness